NUTRITIONAL, ANTIOXIDANT AND SENSORY PROPERTIES OF CEREAL BARS FORTIFIED BY EDIBLE FLOWERS - Ivanišová, Eva; Asante, Esther (Journal on Processing and Energy in Agriculture, 2025)
The aim of this study was to determine the antioxidant activity, total polyphenols, and phenolic acids, as well as total dry matter, fat content, crude protein, and ash content in cereal bars fortified with a 5 % addition of edible flowers. The prepared products were also assessed through sensory evaluation using a 9-point hedonic scale, which considered overall appearance, aroma, taste, consistency, aftertaste, and overall acceptability. The following variants of cereal bars were prepared: a control variant (without added flowers), a variant with elderberry flowers (EF), a variant with lavender flowers (LF), a variant with calendula flowers (CF), and a variant with damascene rose flowers (RD). Antioxidant activity ranged from 3.15 mg TEAC/g (RD) to 0.83 mg TEAC/g (ML). The total polyphenol content ranged from 3.39 mg GAE/g (RD) to 0.91 mg GAE/g (LF; GAE). The content of total phenolic acids was highest in the variant with elderberry flowers (11.80 mg CAE/g) and calendula (9.80 mg CAE/g). The values for total dry matter, fat, and crude protein did not change significantly, remaining at levels of 79 % (dry matter), 15 % (fat), and 12 % (crude protein) in the analyzed samples. The ash content increased with the addition of edible flowers, reaching its highest level in the variant with calendula flowers (2.02 %). The sensory evaluation of the prepared cereal bars indicated that the aroma and taste were characteristic of the flowers, and the consistency was deemed satisfactory.